Does Stepping Stones Triple P plus Acceptance and Commitment Therapy improve parent, couple, and family adjustment following paediatric acquired brain injury? A randomised controlled trial. (October 2015) - Brown, Felicity L.; Whittingham, Koa; Boyd, Roslyn N.; McKinlay, Lynne; Sofronoff, Kate
Abstract: Objective: To evaluate the efficacy of a behavioural family intervention, Stepping Stones Triple P (SSTP), combined with an Acceptance and Commitment Therapy (ACT) workshop in improving parent, family and couple outcomes following paediatric acquired brain injury (ABI). Participants and setting: Fifty-nine parents (90% mothers) of children (mean age 7 years; 35 males, 24 females) with ABI. Intervention: Participants were randomly assigned to a treatment (10-week group SSTP and ACT program) or a care-as-usual (CAU) control condition (10 weeks). Those in the CAU condition received the treatment after the waitlist period. Outcomes: Self-report measures of parent psychological distress, parent psychological flexibility, parenting confidence, family functioning, and couple relationship, assessed at: pre-intervention, post-intervention, and 6-months post-intervention. Results: Post-intervention, the treatment group showed significant, small to medium improvements relative to the CAU group (at the p < .05 level) on parent psychological distress, parent psychological flexibility, parent confidence in managing behaviours, family adjustment, and number of disagreements between parents. Most improvements were maintained at 6-months. Conclusions: Parent skills training and ACT may be efficacious in improving parent, family, and couple outcomes in families of children with an ABI. Highlights: We trialed a parenting intervention for parents of children with acquired brain injury. The intervention led to improvements on parent, family, and couple outcomes. Most improvements were maintained for at least 6-months post-intervention.